2020
DOI: 10.1096/fj.202001855rr
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic therapy ameliorates renal fibrosis postacute kidney injury by alleviating renal senescence

Abstract: Acute kidney injury (AKI) is a common clinical problem, and patients who survive AKI have a high risk of chronic kidney disease (CKD). The mechanism of CKD post‐AKI, characterized by progressive renal fibrosis, is still unclear. Maladaptive tubular epithelial cells (TECs) after AKI are considered a leading cause of renal fibrosis post‐AKI. TECs under maladaptive repair manifest characteristics of senescence. Removing senescent TECs by genetic ablation has been proven effective in reducing renal fibrosis. Senol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 49 publications
3
58
0
Order By: Relevance
“…Senescent cell killing compounds, termed senolytics, are a new category of pharmaceuticals aimed at combating age‐associated diseases, systemically clearing senescent cells by removing the brakes on senescent cell anti‐apoptotic pathways (SCAPs) (Zhu et al, 2015 , 2016 ). The combination of dasatinib and quercetin is especially effective at removing senescent cells in a host of tissues (Chu et al, 2020 ; Li et al, 2021 ; Palmer et al, 2019 ; Zhang, Swarts, et al, 2019 ; Zhu et al, 2015 ), all while improving physical function and extending lifespan (Xu et al, 2018 ). Although there are conflicting reports on the abundance of senescent cells in resting muscle from old mice (Dungan et al, 2020 ; Silva et al, 2019 ), recent studies have demonstrated that 10 days following cardiotoxin injury to muscle, senolytic drugs elevate satellite cell numbers and are associated with a greater number of large myofibers (Doan et al, 2020 ), in addition to reducing the number of SA β‐Gal+ cells in damaged muscle tissue (Chiche et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Senescent cell killing compounds, termed senolytics, are a new category of pharmaceuticals aimed at combating age‐associated diseases, systemically clearing senescent cells by removing the brakes on senescent cell anti‐apoptotic pathways (SCAPs) (Zhu et al, 2015 , 2016 ). The combination of dasatinib and quercetin is especially effective at removing senescent cells in a host of tissues (Chu et al, 2020 ; Li et al, 2021 ; Palmer et al, 2019 ; Zhang, Swarts, et al, 2019 ; Zhu et al, 2015 ), all while improving physical function and extending lifespan (Xu et al, 2018 ). Although there are conflicting reports on the abundance of senescent cells in resting muscle from old mice (Dungan et al, 2020 ; Silva et al, 2019 ), recent studies have demonstrated that 10 days following cardiotoxin injury to muscle, senolytic drugs elevate satellite cell numbers and are associated with a greater number of large myofibers (Doan et al, 2020 ), in addition to reducing the number of SA β‐Gal+ cells in damaged muscle tissue (Chiche et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the glomerular injury may occur after tubular injury [ 58 ]. Finally, antioxidant [ 60 ] and anti-senescence compounds [ 61 , 62 ] partially delayed CKD progression after RLDC treatment, suggesting the involvement of reactive oxygen species and cell senescence in the pathogenesis.…”
Section: Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…Baisantry et al [ 15 ] demonstrated that Atg5 ablation from kidney proximal tubules decreased tubular cell senescence and reduced fibrosis after renal ischemia/reperfusion injury in mice, implying a role of tubular autophagy in senescence and renal fibrosis in post-injury kidneys. More recently, senescent cells in kidneys after repeated low dose cisplatin treatment, which, along with fibrosis, was alleviated by NAC [ 62 ] and intermittent Dasatinib + Quercetin treatment [ 61 ].…”
Section: Autophagy In Aki–ckd Transitionmentioning
confidence: 99%
“…In the past, AKI was thought to be a reversible disease but recent studies show that 20-50% of AKI survivors will progress to chronic kidney disease (CKD) [4]. Patients with AKI may develop CKD, even end-stage kidney disease, even if there is no history of kidney disease, or renal function has partially or fully recovered [4][5][6][7][8][9]. Compared with those without AKI, patients with AKI had an approximately 8-fold increased risk of developing CKD and 3-fold of developing end-stage kidney disease [10].…”
Section: Introductionmentioning
confidence: 99%